2022
DOI: 10.3390/epidemiologia3020014
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Mortality, and Risk Factors of COVID-19 in Nursing Homes

Abstract: During the period from March 2020 to January 2021, we performed an analysis of incidence, mortality, and risk factors of COVID-19 in nursing homes (NHs) in two health departments (HDs) of Castellon (Spain) 2021 through epidemiological surveillance and an ecological design. Laboratory-confirmed COVID-19 cases, cumulative incidence rate (CIR), and mortality rate (MR) of 27 NHs were collected. Information of residents, staff, and facilities was obtained by questionnaire. Multilevel Poisson regression models were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 63 publications
0
24
1
Order By: Relevance
“…As a result, non-profit private as well as publicly owned and administered LTCHs may have had more funding available in times of crisis. However, it is not only financing that makes a difference as publicly administered LTCHs offer more stable job conditions, have higher staff ratios, and demand more professional training and experience [5,8,18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, non-profit private as well as publicly owned and administered LTCHs may have had more funding available in times of crisis. However, it is not only financing that makes a difference as publicly administered LTCHs offer more stable job conditions, have higher staff ratios, and demand more professional training and experience [5,8,18].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted in the Province of Castellón (Spain) showed that a lower ratio of assistant nurses to residents and cumulative COVID-19 incidence in staff were significantly associated with higher mortality after adjusting for LTCH characteristics [18]. Although quantitative data on staff qualifications and working conditions in the Community of Madrid are unavailable, a recently published, large qualitative study conducted an in-depth analysis of the working conditions in LTCHs in several autonomous communities in Spain, including Madrid [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pandemic has been particularly deadly for residents of nursing homes and other long‐term care facilities in the US and in European countries (Shen, 2022). Recent studies have pointed out the heterogeneity of the quality of the nursing homes (Cronin & Evans, 2022), the organization structure of the staff (Dean et al., 2022) and the private ownership of the nursing home (Arnedo‐Pena et al., 2022) as explaining factors of the excess mortality due to COVID‐19. These findings support our analysis of the potential mechanisms behind the excess mortality in nursing homes.…”
Section: Mechanismsmentioning
confidence: 99%
“…Influenza and COVID-19 might be symptomatically identical and lead to more severe-course coinfections, consequences, or death outcomes. Moreover, COVID-19 spreads among high-risk categories the same way as seasonal influenza, which can harm older people and those with chronic comorbidity, including obese people and long-term care patients [ 10 , 11 , 12 , 13 ]. In a Brazilian study assessed by more than 92,000 COVID-19 patients, the death risks were 17% lower, the intensive care requirements were 8%, and the invasive response odds were 18% for those who obtained an influenza vaccine [ 14 ].…”
Section: Introductionmentioning
confidence: 99%